INITIAL DEVELOPMENT OF FIVE TREE SPECIES NATIVE TO THE ATLANTIC FOREST IN RECOMPOSITION PLANTATIONS IN SOUTHERN BRAZIL - Maffra, Charles Rodrigo Belmonte; Turchetto, Felipe; Cantarelli, Edison Bisognin (Floresta, 2020)
The regularization of rural properties in the molds of the New Forest Code depends on the silvicultural study of the native species of the Brazilian biomes. The objective of this study was to evaluate the initial growth of five native tree species of the Atlantic Forest, with a view to their use in forest restoration projects. The following species were produced in the nursery, planted in the field, and evaluated for performance: Araucaria angustifolia, Mimosa scabrella, Trichilia claussenii, Schizolobium parahyba, and Cordia trichotoma. These species were distributed in two different areas, based on the randomized block experimental design. In experiment 1, the species A. angustifolia, M. scabrella, and C. trichotoma were distributed in three randomized blocks, each composed of 11 plants of each species. In experiment 2, the species A. angustifolia, M. scabrella, T. claussenii, and S. parahyba were distributed in three randomized blocks, each one composed of five plants of each species. In general, S. parahyba and M. scabrella showed faster development than the other species and, in this regard, are promising candidates for forest areas constitution or reconstitution in which there is interest in obtaining economic returns in less time. Araucaria angustifolia and T. claussenii showed relatively low development, whereas C. trichotoma showed intermediate development in relation to the other species studied. Despite their differences in performance, all species proved to be suitable for use in reforestation, mainly in the region where the study was developed.